2015
DOI: 10.1667/rr13732.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Gamma-Irradiation Induces a Dose-Rate-Dependent Pro-inflammatory Response and Associated Loss of Function in Human Umbilical Vein Endothelial Cells

Abstract: A central question in radiation protection research is dose and dose-rate relationship for radiation-induced cardiovascular diseases. The response of endothelial cells to different low dose rates may contribute to help estimate risks for cardiovascular diseases by providing mechanistic understanding. In this study we investigated whether chronic low-dose-rate radiation exposure had an effect on the inflammatory response of endothelial cells and their function. Human umbilical vein endothelial cells (HUVECs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…The pro-inflammatory effect of X-ray exposure was previously evidenced in the same in vitro model (Baselet et al, 2017 ). In accordance, others observed elevated IL-6 and IL-8 levels in 2–10 Gy X-ray-irradiated EC cultures (Meeren et al, 1997 ), elevated IL-6 levels in EC cultures after chronic irradiation with a total dose of 2 Gy (Ebrahimian et al, 2015 ) and elevated blood levels of IL-6 were detected in A-bomb survivors (Hayashi et al, 2003 ). These changes were previously demonstrated to increase EC adhesiveness to monocytes 1 day after exposure to X-ray doses higher than 5 Gy (Khaled et al, 2012 ).…”
Section: Discussionsupporting
confidence: 67%
“…The pro-inflammatory effect of X-ray exposure was previously evidenced in the same in vitro model (Baselet et al, 2017 ). In accordance, others observed elevated IL-6 and IL-8 levels in 2–10 Gy X-ray-irradiated EC cultures (Meeren et al, 1997 ), elevated IL-6 levels in EC cultures after chronic irradiation with a total dose of 2 Gy (Ebrahimian et al, 2015 ) and elevated blood levels of IL-6 were detected in A-bomb survivors (Hayashi et al, 2003 ). These changes were previously demonstrated to increase EC adhesiveness to monocytes 1 day after exposure to X-ray doses higher than 5 Gy (Khaled et al, 2012 ).…”
Section: Discussionsupporting
confidence: 67%
“…Our current study is in line with some of the previously reported results, and we demonstrated that chronic external low-dose (150 mGy) irradiation at a low-dose rate (28 iGy.h-1) induces a protective effect in atherosclerotic lesions. The importance of the dose, as well as the dose rate, even after chronic low-dose exposure, was confirmed in animal models (19) and in a cultured endothelial cell model (24,36).…”
Section: Figmentioning
confidence: 80%
“…These results suggest that low doses of radiation have an effect that is opposite of that from high doses in atherosclerosis development, and that dose rate is a very important parameter to consider. Dose rate dependent of inflammatory response and endothelial cell function has been demonstrated recently in published in vitro experiments (24).…”
mentioning
confidence: 78%
“…In vitro studies showed that chronic LDR delivered at 4.1 mGy/h had harmful effects on human umbilical vein endothelial cells (HUVECs; premature senescence, loss of capacity to form vascular networks, and secretion of pro-inflammatory molecules) when the total dose was >2 Gy, while a lower dose rate (1.4 mGy/h) did not induce damage even at a dose of 2 Gy. 17 , 18 Moreover, Rombout et al showed that a low dose (0.05 Gy) induced subtle increases in DNA double-strand breaks in HUVECs compared to high doses. 19 Also, Rödel et al showed that acute radiation doses in the range of 0.3 to 0.7 Gy induced anti-inflammatory effects on human endothelial cells (EA.Hy926) by stimulating protein and mitochondrial RNA (mRNA) levels of transforming growth factor-β 1 (TGF-β1), leading to downregulation of leukocyte adhesion .…”
Section: Introductionmentioning
confidence: 99%